Physical, mental and behavioral health indicators in relation to academic performance in European boys and girls: the I.Family study - Qinyun Lin; Monica Hunsberger; Sofia Klingberg; Stefaan de Henauw; Antje Hebestreit; Fabio Lauria; Artur Mazur; Luis Moreno; Kurdiné Molnár Eszter Noémi; Iris Pigeot; Michael Tornaritis; Toomas Veidebaum; et al. (BMC Public Health, 2025)
Abstract Background Academic performance in children is associated with a range of health-related factors, including physical fitness, mental well-being, sleep, and behavioral patterns. While previous studies have examined these factors individually, fewer have assessed their independent associations with academic achievement while accounting for other relevant health indicators. This study uses data from the I.Family study to explore how physical, mental, sleep-related, and behavioral health indicators relate to academic achievement among European adolescents, considering each factor’s contribution while adjusting for the others. Methods We used data from the 2013–2014 wave of the I.Family study to investigate eight health indicators: health related quality of life (HRQoL), body mass index (BMI), diet, media use, physical activity, sleep duration and quality, and stressful life events. Their associations with self-reported academic performance in mathematics and language were analyzed using binary logistic regression models, adjusting for confounders such as parents’ education, income, survey country and child’s age. We conducted separate analyses for girls and boys to capture associations that are specific to academic subject and sex. Results A number of significant associations were found between several health indicators and academic performance. Higher HRQoL scores, reduced media time, and increased physical activity were linked to better academic performance in both mathematics and language for both boys and girls. Variation by sex and academic subjects were observed, with lower BMI, higher healthy diet scores and better sleep quality associated with better academic performance in language among girls. For mathematics, emotional, self-esteem, and family-related HRQoL were all significantly associated with higher performance for both boys and girls. In contrast, for language achievement, only family-related HRQoL was significant for both sexes. Conclusions Our study underscores the need to consider both the importance of accounting for heterogeneity in sex and the differences between math and language academic subjects when investigating determinants of academic performance, setting the stage for further research on this topic to explore potential competing, synergistic, or time-dependent effects among these different health dimensions.